The Effect of Core Stability Training on Shooting Accuracy and Balance in Petanque Athletes - Rasyono , Rasyono; Ihsan, Fadli; Erhan Orhan, Bekir; Indra Bayu, Wahyu; Yusfi, Herri (International Journal of Sport Studies for Health, 2026)
Objective: Petanque is a precision sport that requires postural stability and precise motor control. Core stability, which encompasses the strength and coordination of the trunk and pelvic muscles, is considered fundamental in maintaining balance and improving technical performance, particularly in shooting movements. Core stability training, though, has not yet been extensively implemented in petanque training programs. This research aimed to examine the impact of a core stability training program on petanque athletes’ shooting accuracy and balance (static and dynamic). Methods & Materials: A quasi-experimental design was employed with 20 petanque athletes aged between 14 and 25, who were assigned to either an experimental group (n = 10) or a control group (n = 10). The experimental group received a 6-week core stability exercise program (three times a week), whereas the control group continued regular training without intervention. Pre- and post-tests were administered using a shooting accuracy test, One-Leg Stance Test (static balance), and Y-Balance Test (dynamic balance). Paired and independent t-tests were used to analyze data with a significance level of p < 0.05. Results: The intervention group demonstrated significant improvements in shooting accuracy (p = 0.000), static balance (p = 0.000), and dynamic balance (p = 0.000), whereas the control group showed no significant changes. Additionally, inter-group comparisons conducted after the test revealed significant differences in all variables in favour of the experimental group. Conclusion: Core stability training significantly enhances shooting accuracy and both forms of balance in petanque athletes. Integrating structured core training into regular conditioning routines is recommended to optimise technical performance and physical control in precision-based sports.